2019
DOI: 10.1186/s13052-019-0693-z
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin serum levels and coexistence with Hashimoto’s thyroiditis as predictors of malignancy in children with thyroid nodules

Abstract: Thyroid cancer (TC) in childhood is a rare disease characterized by an excellent prognosis. Thyroid nodules in children, although less common than in adults, have a greater risk of malignancies, particularly in those cases associated with anamnestic, clinical and ultrasonographic risk factors. Among the factors, which have been found to be linked with an increased relative risk of TC in children, an important role seems to be possibly played by an underlying nodular Hashimoto’s thyroiditis (HT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 3 , 4 There is thus a close relationship between the pathogeneses of these two diseases. Although the exact mechanism linking these diseases is not clear, there are currently three main hypotheses: 1) HT is a precancerous lesion of PTC; 2 , 23 2) the hypothesis of chronic inflammation; and 3) HT and PTC have common causes, potentially including immune factors (both thyroid globulin antibody and microsomal antibody have been found in the blood of HT and PTC patients), 24 26 endocrine factors (HT can cause hypothyroidism and increase reactive thyrotropin, which can in turn cause carcinogenesis), 27 31 and radioactive factors (exposure to X-rays can lead to thyroid inflammation and carcinogenesis, via the same mechanism). 32 37 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 There is thus a close relationship between the pathogeneses of these two diseases. Although the exact mechanism linking these diseases is not clear, there are currently three main hypotheses: 1) HT is a precancerous lesion of PTC; 2 , 23 2) the hypothesis of chronic inflammation; and 3) HT and PTC have common causes, potentially including immune factors (both thyroid globulin antibody and microsomal antibody have been found in the blood of HT and PTC patients), 24 26 endocrine factors (HT can cause hypothyroidism and increase reactive thyrotropin, which can in turn cause carcinogenesis), 27 31 and radioactive factors (exposure to X-rays can lead to thyroid inflammation and carcinogenesis, via the same mechanism). 32 37 …”
Section: Discussionmentioning
confidence: 99%
“…TSH has a major role on the proliferation and functioning of thyroid cell and persistently elevated TSH levels increase the risk of DTC formation ( 28 ). Even patients with a nodule and TSH levels in upper tertiles of reference range may have increased risk for malignancy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Co-existence of DTC and HT has been reported in many publications ( 33 , 34 ). However, it is not clear whether lymphocytic infiltration due to HT facilitates DTC formation or the immune response against the tumour initiates lymphocytic infiltration ( 28 ). Adult studies that have investigated the prevalence of HT among patients with DTC have reported a variable prevalence of 5-85% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetics differ in pediatric and adult TC [55]. Mutations in RAS, BRAF , PAX8 , or PPARG genes while frequently found in adults are rare in pediatric TC where RET/PTC , AKAP9–BRAF , and NTRK1 rearrangements prevail [28, 56].…”
Section: Interrelations Of Stress Autoimmunity Inflammation and Tumor...mentioning
confidence: 99%